Skin tests in bird breeder's disease. Issue 7 (July 1986) - Morell, F; Curull, V; Orriols, R; De Gracia, J
Abstract : The diagnostic value of skin tests was assessed in 35 patients affected by bird breeder's disease by comparing the results with those obtained in a group of 27 symptomless breeders and 10 symptomless unexposed individuals. Sterilised and diluted serum and lyophilised extracts of faeces prepared from the breeder's own birds were injected intradermally. Skinprick tests using the same materials were carried out simultaneously. The intradermal test using serum showed a positive reaction in 18 out of 20 patients tested and in three out of 20 symptomless breeders (p less than 0.0005); later reactions occurred in eight of the patients and one of the symptomless breeders (p less than 0.01). A delayed reaction was seen in five of the patients and one of the symptomless breeders (p = 0.09). No positive reactions were recorded in symptomless unexposed individuals. Intradermal skin testing using extracts of faeces yielded an immediate reaction in 19 of 21 patients and in three of 11 symptomless breeders tested (p less than 0.001); a late reaction was seen in 18 of the patients and in five of the symptomless breeders (p less than 0.05). Delayed reactions occurred in 11 of the 21 patients tested, whereas no positive responses were seen in symptomless breeders (p less than 0.025). Skinprick tests gave negative results in all cases. Skin testing constitutes a simple, quick, and safe procedure that can assist the differential diagnosis between individuals with bird breeder's disease and symptomless breeders, the immediate reaction being similar in its sensitivity to testing for serum precipitins but possessing greater specificity.